Profesor carskiego uniwersytetu Warszawskiego Aleksandr Martinowicz Pridik. Główne etapy działalności naukowej i dydaktycznej - Surienowicz Kazorow, Sarkis (Studia Europaea Gnesnensia, 2016)
The article discusses the life as well as academic and teaching work of Alexandr Martinovich Pridik, professor of Old Greek literature at the University of Warsaw. The author used previously unpublished archival material as well as writings of the academician. A.M. Pridik was in fact the only Professor of the University of Warsaw (later the Donskoy University) who succeeded in fleeing Bolshevik Russian and later continued his scholarly and teaching activities in Estonia, which by then had gained independence.